Reimagining liberation : how Black women transformed citizenship in the French empire - Joseph-Gabriel, Annette K. (New Black studies series., 2020)
"The book tells the stories of seven women who played important roles in the decolonization enterprise in the mid-twentieth century-roles that have often been overlooked or underestimated in retrospective analyses. The author delves into lives of women who were injured by German torpedoes, incarcerated in concentration camps, or declared enemies of the Vichy state in order to thoroughly examine the role of black women in the discursive framing of citizenship in the Francophone world. Marshaling new evidence from archives in France, Haiti, Martinique, and the United States, Joseph-Gabriel reveals that black women played central roles in anticolonial movements and articulated a de-colonial citizenship that was more inclusive because it was informed by the intersecting oppressions they faced in the French empire. The author argues that black women used the language of citizenship to claim their belonging to multiple cultural and political spaces at once (France, Africa, the Caribbean, the African diaspora, the global South) and in so doing they expanded the possibilities of citizenship beyond the borders of the nation state and the French empire to imagine Pan African, Pan Caribbean, and global South identities that were informed by a feminist practice of anticolonial resistance"--